Avoiding chemotherapy prescribing errors: Analysis and innovative strategies. Issue 9 (29th January 2019) - Reinhardt, Heike; Otte, Petra; Eggleton, Alison G.; Ruch, Markus; Wöhrl, Stefan; Ajayi, Stefanie; Duyster, Justus; Jung, Manfred; Hug, Martin J.; Engelhardt, Monika
Abstract: Background: At Freiburg University Medical Center, chemotherapy prescriptions are processed via a computerized physician order entry (CPOE) tool and clinically checked by a designated chemotherapy surveillance team. Any error detected is reported instantly, corrected, and prospectively recorded. The objective of the current study was to gain insight into the causes, potential consequences, and future preventability of chemotherapy prescribing errors. Methods: A detailed analysis of 18, 823 consecutive antineoplastic orders placed in 2013 through 2014 was performed. In cooperation with information technology (IT) specialists, the intercepted errors were analyzed for effective future prevention using IT measures. Potential error consequences were determined by case discussions between pharmacists and physicians. Results: Within 24 months, a total of 406 chemotherapy prescribing errors were intercepted that affected 375 (2%) of the total orders. Errors were classified as clinically relevant in 279 of the chemotherapy orders (1.5%). In these cases, reduced therapeutic efficacy (0.44%), the need for increased monitoring (0.48%), prolonged hospital stay (0.55%), and fatality (0.02%) were avoided as potential consequences. The most efficient conventional measures for error prevention comprised checking the order history and patient's medical record, and a detailed knowledge of chemotherapy protocols. Of all the errors analyzed, 61% would be avoided through further software development. The improvements identified are implemented through a validated next‐generation CPOE tool. Conclusions: The upgraded CPOE tool can be shared across other hospitals to raise safety standards and spread potential benefits across a wider patient population. The current analysis also highlighted that approximately 30% to 40% of errors cannot be avoided electronically. Therefore, pharmacovigilance initiatives remain indispensable. Abstract : Chemotherapy prescribing errors are a potential threat to patient safety. The current study demonstrates how a system of control mechanisms combined with information technology has the potential to efficiently reduce patient harm when shared across a wider range of cancer services.